Inhibition of serum and glucocorticoid regulated kinases by GSK650394 reduced infarct size in early cerebral ischemia-reperfusion with decreased BBB disruption. (25th September 2021) - Chi, Oak Z.; Chiricolo, Antonio; Liu, Xia; Patel, Nikhil; Jacinto, Estela; Weiss, Harvey R.
Graphical abstract: Highlights: Inhibition of SGK1 decreased infarct in early cerebral ischemia-reperfusion. Inhibition of SGK1 decreased BBB disruption in early cerebral reperfusion. Decreased MMP2 by GSK650394 could be one of the mechanisms of the BBB protection. Inhibition of SGK1 may be neuroprotective within the first few hours of stroke. Abstract: Blood-brain barrier (BBB) disruption is one of the most important pathological changes following cerebral ischemia-reperfusion. We tested whether inhibition of the serum and glucocorticoid regulated kinase 1 (SGK1) would decrease BBB disruption and contribute to decreasing infarct size in the first few hours of cerebral ischemia-reperfusion within the thrombolysis therapy time window. After transient middle cerebral artery occlusion (MCAO), an SGK1 inhibitor GSK650394, or vehicle was administered into the lateral ventricle of rats. After one hour of MCAO and two hours of reperfusion, we determined BBB disruption using the transfer coefficient (Ki ) of 14 C-α-aminoisobutyric acid, and also determined infarct size, phosphorylation of NDRG1, and MMP2 protein level. Ischemia-reperfusion increased (+34%, p < 0.05) and GSK650394 decreased (−25%, p < 0.05) the Ki in the ischemic-reperfused cortex. GSK650394 decreased the percentage of cortical infarct (−31%, p < 0.001). At the same time GSK650394 reduced NDRG1 phosphorylation and MMP2 protein level in the ischemic-reperfused cortex suggesting that SGK1 was inhibited by GSK650394 and that lower MMP2 could be one of the mechanisms of decreased BBB disruption. Collectively our data suggest that GSK650394 could be neuroprotective and one of the mechanisms of the neuroprotection could be decreased BBB disruption. SGK1 inhibition within the thrombolysis therapy time window might reduce cerebral ischemia-reperfusion injury.